Quality assessment of growing media based on bottom sediment in agriculture: the content of elements and radionuclides - Baran, Agnieszka; Mugisha, Axelle; Doleželová, Eva; Szarłowicz, Katarzyna; Ryant, Pavel; Birch, Gavin (Environmental geochemistry and health, 2025)
The aim of the studies was to evaluate the content of macroelements, trace elements, and radionuclides in mixtures of bottom sediments (BS) with dolomite (D), sewage sludge (SS), and biochar (BC). The bottom sediment was mixed with side products in the ratio of 80% bottom sediment and 20% dolomite, sewage sludge and biochar respectively. After the experiment, chemical analyses were conducted on the growing medium and plant material. The properties of the mixtures showed a high content of TOC and an alkaline and slightly acidic reaction. The highest content of macronutrients was found in the mixtures of bottom sediments and dolomite (Ca, Mg) and in the mixtures of bottom sediments and sewage sludge (S, P). The use of mixtures reduced the content of toxic elements, such as Cd and Pb in the biomass. In the mixed samples, it was also found that the content of natural radionuclides decreased in most of the samples analysed. An exception was the BS+BC mixture, since in this system an increase in 137Cs and 210Pb was observed. The heavy metal content in the mixtures was below toxic limits and the addition of sewage sludge, dolomite, and biochar to the sediment did not increase its radioactivity to dangerous levels. The bottom sediment-based mixture suitable for use in agriculture and would not pose an environmental risk. However, the analysed mixtures based on bottom sediments and waste cannot replace fertilisers due to low total content of nutrients.
Keywords: hořčík; Metals, Heavy; Trace Elements; Chemical composition; odpadní vody; Agriculture; radionuklidy; uhličitan vápenatý; Sewage; zemědělství; Pollution; Geologic Sediments; Radioisotopes; těžké kovy; Growing medium; Bottom sediments; geologické sedimenty; Nutrients; dřevěné a živočišné uhlí; Magnesium; Calcium Carbonate; Charcoal; stopové prvky; Side products